Interprofesional Education (IPE) Sebagai Upaya Membangun Kemampuan Perawat Dalam Berkolaborasi Dengan Tenaga Kesehatan Lain - Puput Risti Kusumaningrum; Anggorowati Anggorowati (Persatuan Perawat Nasional Indonesia Jawa Tengah, 2018)
Background: Qualified health services are a demand for health care providers in the global era. Qualified health services can be achieved through collaborative practices. Integrated education which was initiated as a collaboration media according to WHO is Interprofessional Education (IPE). IPE is a process where a group of students or health workers with different backgrounds learn together for a certain period of time during education, with interaction as the main goal, for collaboration in providing preventive, promotive, rehabilitative and other health services (WHO, 2010). The concept of IPE learning can be applied in 3 activities, namely learning in hospitals, academics, and communities. IPE learning in hospitals that runs well is expected to produce professionals in the health sector who are able to collaborate with other health professions so that they can participate in health development in Indonesia. Objective: a Literature review to find out whether IPE can build nurses' ability to collaborate with other health teams. Method: This literature review was conducted by searching publication articles on EBSCO, Google search, PubMed, Sciencedirect.com with selected keywords namely interprofessional education (IPE), collaboration, interprofessional collaboration (IPC). The searching was done by limiting publications from 2010-2015. Results: From the literature search results that IPE can effectively build the ability of nurses to collaborate with other health workers. It is expected that the IPE implementation can be carried out continuously with more optimal preparation, considering that health institutions are the main providers of prospective professional health workers.